SYNCHRONOUS VIRTUAL CLASSROOM MANAGEMENT: CHALLENGES AND COPING STRATEGIES OF PRE-SERVICE ENGLISH TEACHERS - Afrillia Nurfauziah; Maman Suryaman; Mobit Mobit (IKIP Siliwangi, 2022)
The aim of this study is to explore pre-service English teachers’ experience in facing challenges and their coping strategies in managing synchronous virtual classrooms during practicum. This study employed narrative inquiry as its research design with thematic analysis for analyzing the data collected through semi-structured interviews with three pre-service English teachers. The study found that the pre-service English teachers encountered several problems in managing synchronous virtual classrooms, such as 1) students’ negative attitude; 2) insufficient instruction time; 3) lack of relationship or connection between teacher and students; 4) lack of proper feedback from mentor teacher and supervisor. Despite of several challenges mentioned above, the pre-service teachers had some strategies to deal with them, as follows 1) seeking emotional support from peers; 2) actively communicating with expert teachers; 3) solving problems through networking; 4) improving their strategies and skill. In summary, even though the pre-service English teachers faced several challenges, they could manage to overcome such challenges by identifying their needs and available access to improve their classroom situation. Keywords: Challenges, Coping Strategies, Teaching Practicum, Virtual Classroom Management